Histological changes in the gills and liver of a Nile tilapian (Oreochromis niloticus) exposed to Cat Whisker leaf extract (Orthosiphon aristatus) - Ismiyanti, Ismiyanti; Djawad, Muhammad Iqbal; Anshary, Hilal (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2025)
Bacterial infectious diseases are a serious obstacle in the cultivation of tilapia (Oreochromis niloticus). The use of herbal ingredients such as cat whisker leaves (Orthosiphon aristatus) is an alternative to environmentally friendly treatment because of its antibacterial compound content. This study aims to analyze the antibacterial activity of cat whisker leaf extract against Pseudomonas aeruginosa bacteria and its effect on the histopathology of liver organs and gills of tilapia. This study used an experimental method with 4 extract dose treatments (50 ppm, 75 ppm, 100 ppm, and 125 ppm) and negative controls, each with 3 replicates. The first stage included the extraction of cat whisker leaves with ethanol solvent, determination of minimum inhibition concentrations through Optical Density (OD) observation using UV/Vis spectrophotometry, and LC-50 24-hour toxicity test. The second stage involves bacterial infection in fish, followed by soaking in the extract for 24 hours and maintenance for 7 days. The parameters observed included histopathology of the liver and gills and survival rate (SR). The results showed that cat whisker leaf extract was able to inhibit the growth of Pseudomonas aeruginosa, which can be seen from the difference in the degree of histological damage to the liver and gills between treatments. The highest survival of tilapia at the end of the maintenance period was found at a dose of 100 ppm with a value of 90% which is the optimal dose to improve the survival of infected fish.